Islamic Ecological Principles in Muslim Environmentalism Narratives for Religious Moderation in Indonesia - Suprianto, Bibi; Triandini, Yuni; Abdullah, Irwan; Astuti, Tri Marhaeni Pudji (International Journal of Islamic Studies Higher Education, 2023)
Muslim environmentalism in building religious moderation in Indonesia does not only discuss religious issues but also environmental issues that can affect the harmony of humans, religion, and the environment. This study aims to look at the role of Muslim environmentalism in building religious moderation in Indonesia. This study argues that Islam has taught Muslims to care for the environment and care for humans to moderate humans and the environment. Therefore, this study formulates a question how the role of Muslim environmentalism in building religious moderation in Indonesia and how to understand the principle of ecology in Islam as part of the principle of religious moderation. This study uses library research and social media studies that explain in detail the narrative and argumentation of religious moderation. The results show that the role of Muslim environmentalism in building religious moderation narratives shows that; i) the existence of environmental narratives in Islamic views as an effort to form human, religious, and environmental solidarity; ii) the concept of balance as a concept of religious moderation in Islam; iii) the existence of ecological principles in Islam related to the principle of religious moderation. With these results, it is concluded that the role of Muslim environmentalism in building religious moderation shows that Muslims can provide knowledge not only to minimize the occurrence of environmental crises but also as an effort to build religious moderation in Indonesia.